IMPACT OF SUSTAINABLE TOURISM IN THE TRAVEL INDUSTRY - Sofronov, Bogdan (Annals of Spiru Haret University. Economic Series, 2017)
Sustainable tourism is the concept of visiting a place as a tourist and trying to make only a positive impact on the environment, society and economy. A key aspect is respect for the people who call the location home, the culture and customs of the area, and the socio-economic system. While sustainable tourism is sometimes confused with ecotourism, ecotourism is actually only one aspect of sustainable tourism. Sustainable tourism is attempting to have a low impact on the environment and local culture, while helping to generate future employment for local people. The aim of sustainable tourism is to ensure that development brings a positive experience for local people, tourism companies and the tourists themselves.